How to Educate Entrepreneurs? - Georg von Graevenitz; Richard Weber (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2011)
Entrepreneurship education has two purposes: To improve students' entrepreneurial skills and to provide impetus to those suited to entrepreneurship while discouraging the rest. While entrepreneurship education helps students to make a vocational decision its effects may conflict for those not suited to entrepreneurship. This study shows that vocational and the skill formation effects of entrepreneurship education can be identified empirically by drawing on the Theory of Planned Behavior. This is embedded in a structural equation model which we estimate and test using a robust 2SLS estimator. We find that the attitudinal factors posited by the Theory of Planned Behavior are positively correlated with students' entrepreneurial intentions. While conflicting effects of vocational and skill directed course content are observed in some individuals, overall these types of content are complements. This finding contradicts previous results in the literature. We reconcile the conflicting findings and discuss implications for the design of entrepreneurship courses.
urn:nbn:de:bvb:19-epub-12280-9
Keywords: 650; Gründungsausbildung; Berufsbildung; Qualifikation; Theory of Reasoned Action; Strukturgleichungsmodell; Deutschland